Odontia aculeata and O. sparsa, two new species of tomentelloid fungi (Thelephorales, Basidiomycota) from the secondary forests of northeast China - Yuan, Yuan; Wu, Fang; Dai, Yu-Cheng; Qin, Wen-Min; Yuan, Hai-Sheng (Phytotaxa, 2018)
Two new tomentelloid basidiomycetes, Odontia aculeata and O. sparsa, are described from secondary forests of northeastern China. Odontia aculeata is characterized by resupinate, arachnoid and brownish basidiocarps, a hydnoid hymenophore, a differentiated dimitic hyphal structure in the rhizomorphs with clamp connections on the generative hyphae, a monomitic hyphal system in the subiculum and irregular subglobose basidiospores with verruculose ornamentation. O. sparsa is characterized by resupinate, arachnoid, continuous and brown basidiocarps, smooth or with sparsely distributed spines, a differentiated dimitic hyphal structure in the rhizomorphs with simple-septate generative hyphae, a dimitic hyphal system in the subiculum and verruculose basidiospores. Molecular phylogeny inferred from internal transcribed spacer (ITS) sequences data indicated that the two new species clustered with the other species of Odontia with strong support. These two new species are described and illustrated in this paper.